Family contact in juvenile confinement facilities: Analysis of the likelihood of and barriers to contact. Issue 5 (4th July 2019) - Mikytuck, Alyssa M.; Woolard, Jennifer L.
Abstract: Although family relationships are important for incarcerated adolescents, little is known about barriers and facilitators of family contact. The present study used the Survey of Youth in Residential Placement (SYRP) to analyze frequency of, predictors of, and barriers to in-person contact and phone contact. Family travel time and race predicted type and frequency of contact. White youth were more likely to report multiple forms of contact and more frequent contact than other groups. Travel time to the facility also predicted financial barriers to contact. These results are discussed in light of the numerous family focused initiatives underway at juvenile facilities.